2000
DOI: 10.1128/jcm.38.11.3919-3925.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Protease and Reverse Transcriptase Sequences in Non-Subtype-B Human Immunodeficiency Virus Type 1 Strains: Evidence of Many Minor Drug Resistance Mutations in Treatment-Naive Patients

Abstract: Most human immunodeficiency virus (HIV) drug susceptibility studies have involved subtype B strains. Little information on the impact of viral diversity on natural susceptibility to antiretroviral drugs has been reported. However, the prevalence of non-subtype-B (non-B) HIV type 1 (HIV-1) strains continues to increase in industrialized countries, and antiretroviral treatments have recently become available in certain developing countries where non-B subtypes predominate. We sequenced the protease and reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(63 citation statements)
references
References 38 publications
3
59
0
1
Order By: Relevance
“…The growing number of studies on non-B HIV-1 subtypes has indicated the presence of several polymorphisms in PR region. The limited data about predominant subtypes of this study, CRF06_cpx, from Burkina Faso, France, Italy, and Australia suggest that in this regard this subtype is not different from others [Vergne et al, 2000;Montavon et al, 2002;Monno et al, 2005;Lawrence et al, 2006;Ndembi et al, 2008] On the other hand, PR polymorphisms G17E and L63H also frequently seen by us have been rarely found in other subtypes or CRFs [Kantor et al, 2005;van de Vijver et al, 2006], (http://hivdb.stanford.edu/). Despite the clinical relevance of several PR polymorphisms being largely unknown, some studies have shown that the outcome of ART is dependent on the viral subtype [Perno et al, 2001;Kantor et al, 2005;Pillay et al, 2005].…”
Section: Discussionmentioning
confidence: 50%
“…The growing number of studies on non-B HIV-1 subtypes has indicated the presence of several polymorphisms in PR region. The limited data about predominant subtypes of this study, CRF06_cpx, from Burkina Faso, France, Italy, and Australia suggest that in this regard this subtype is not different from others [Vergne et al, 2000;Montavon et al, 2002;Monno et al, 2005;Lawrence et al, 2006;Ndembi et al, 2008] On the other hand, PR polymorphisms G17E and L63H also frequently seen by us have been rarely found in other subtypes or CRFs [Kantor et al, 2005;van de Vijver et al, 2006], (http://hivdb.stanford.edu/). Despite the clinical relevance of several PR polymorphisms being largely unknown, some studies have shown that the outcome of ART is dependent on the viral subtype [Perno et al, 2001;Kantor et al, 2005;Pillay et al, 2005].…”
Section: Discussionmentioning
confidence: 50%
“…We are aware that the phylogenetic analysis of the pol gene for HIV-1 subtyping provides only partial information, and the possibility does exist that other regions might pertain to different subtypes. Nevertheless, a number of recent studies successfully adopted this approach to evaluate the spread of non-B variants in previously B-restricted countries [Vergne et al, 2000;Balotta et al, 2001;Gonzales et al, 2001;Papa et al, 2002]. Moreover, our data can be considered reliable because of the high concordance between the countries of origin of the patients and the most common viral strains circulating within those countries.…”
Section: Discussionmentioning
confidence: 89%
“…Historically, HIV-1 subtypes have been phylogenetically classified according to sequence variation within the env gene [McCutchan et al, 1996]. However, reverse transcriptase (RT) and protease (PR) genes of isolates throughout the world differ from one another, thereby allowing subtype grouping [Vergne et al, 2000;Gonzales et al, 2001]. Consequently, pol sequences, now readily available to clinicians for the evaluation of antiretroviral drug susceptibility, may permit the concurrent identification of HIV subtypes without additional costs.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, viral RNA was extracted from the plasma using the QIAamp Viral RNA kit (Qiagen, Courtaboeuf, France), and amplified fragments covering the viral protease (amino acids 1Á99) and reverse transcriptase (amino acids 1Á310) were generated with outer G25REV-IN3 and inner AV150-polM4 primers. The assay detected mutants that comprise at least 20% of the virus population [10]. Amino acid sequences were analyzed to identify relevant drug resistance mutations (DRMs), using the Agence Nationale de Recherche sur le Sida et les Hépatites (ANRS) interpretation algorithm, version May 2011 (http://www.hivfrenchresistance.org/).…”
Section: Sample Processing Viral Load and Genotyping Testingmentioning
confidence: 99%